The Consequences of Diversifying the US District Courts: Race, Gender, and Ideological Alignment through Judicial Appointments. (2nd October 2021) - Hofer, Scott; Achury, Susan
Abstract: The American judiciary has seen a significant rise in diversity with active efforts by presidents to confirm women and racial minorities to the bench, yet a lack of representation remains an issue. While most of the scholarship on the influx of jurists from diverse backgrounds is centered on identifying differences in judicial decision making, we empirically test the impact of racial and gender diversification on the ability of selectors to influence case outcomes by nominating ideologically-aligned judges. Does the selection of judges from underrepresented backgrounds affect the ability of the elected branches to align their ideological preferences on the federal bench? We argue that differences in uncertainty, network integration, and ideological availability within the candidate pool can make it more difficult for selectors to predict the ideological preferences of racial minorities; therefore, their decisions on the bench are less aligned with their selectors' preferences. Using case outcomes on the federal district courts (1985–2012), we find that decisions adopted by White judges tend to closely align with the ideological preferences of their selectors regardless of their gender; however, the ideology of selectors has no relationship with decisions adopted by most jurists of color, with the exception of Latinas and Asian-Americans. Our results show that diversifying the bench has an ideological cost for the political actors involved in the appointment of district court judges. Weak links between the ideology of the selectors and the behavior of the judges mean lower judicial deference to political actors, and to that extent, the judiciary may become more independent of ongoing ideological battles in American politics.